Pengaruh Iklan Terhadap Keputusan Pembelian Produk Smartphone Oppo Di IT Center Manado - Moloku, Serina O.; Tampi, Johny R. E.; Walangitan, Olivia Ch. F. (JURNAL ADMINISTRASI BISNIS, 2019)
The purpose of this study is to find out whether there is an influence of advertising on the decision to buy oppo smartphone products at the Manado IT Center. The approach of this research is a quantitative approach. The independent variable is advertising and the dependent variable is a purchasing decision. The population in this study were oppo smartphone users in the city of Manado who had bought Oppo smartphone products at the Manado IT Center. The population in this study is infinite. Sampling uses probability sampling. The sampling technique uses incidental sampling techniques. The total sample of respondents is 100 people. The method of data collection is through questionnaires, observation and documentation. The research instrument uses a Likert scale. Test instruments used validity test and reliability test. Data analysis used using simple linear regression analysis. Data processing is used by the SPSS 25 program. The results of the study are obtained is the value of the coefficient between advertising and purchasing decisions including low of 0.394, The effect of advertising on purchasing decisions is very low at 0.1555 and the results of simple linear regression analysis obtained a positive regression coeficient so that the direction of the influence of advertising variables on the variable buying decision is positive.